2011
DOI: 10.1590/s1516-31802011000600007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lower-limb dominance on postural balance

Abstract: CONTEXT AND OBJECTIVE: Maintainance of postural balance requires detection of body movements, integration of sensory information in the central nervous system and an appropriate motor response. The purpose of this study was to evaluate whether lower-limb dominance has an influence on postural balance. DESIGN AND SETTING: This was a cross-sectional study conducted at Faculdade de Medicina da Universidade de São Paulo (FMUSP) and at Hospital do Coração (HCor). METHODS: Forty healthy sedentary males aged 20 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 9 publications
11
33
2
7
Order By: Relevance
“…These studies have shown no differences between the limbs for the risk factors for ankle sprain, such as ankle strength and postural balance measures. Although muscle latency is not directly linked with strength and balance, our results showing no difference between the limbs in muscle latency correlate with those of previous studies with respect to limb dominance (17)(18)(19). Limb dominance was studied by Lin et al (17).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These studies have shown no differences between the limbs for the risk factors for ankle sprain, such as ankle strength and postural balance measures. Although muscle latency is not directly linked with strength and balance, our results showing no difference between the limbs in muscle latency correlate with those of previous studies with respect to limb dominance (17)(18)(19). Limb dominance was studied by Lin et al (17).…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary to some studies showing differences in muscle latency and balance between the limbs in physically active individuals (15,16), comparisons between the limbs in terms of ankle muscle strength or balance represented no differences in sedentary individuals (17)(18)(19). Similarly, because of the anticipation that similar demands would be placed on the non-dominant and dominant ankles in sedentary individuals, we hypothesized that muscle latency and proprioceptive ability also would not be different between the limbs in sedentary individuals.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations